Eksperimen model pembelajaran MMP dan Problem Solving terhadap kemampuan pemecahan masalah siswa - Nurhaliza, Ika Risti; Maryam, Isnaeni (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The purpose of this study was to determine whether the mathematics problem-solving abilities of students who received the Missouri Mathematics Project (MMP) learning model were better than the mathematics problem-solving abilities of students who received the Problem Solving learning model. The research was conducted at MTs Al-Iman Bulus Purworejo class IX A and IX B. The research method used was a quasi-experimental design, which refers to the instrument of students' mathematical problem-solving abilities. The study population came from grade IX students, with a total of 401 students. The sampling technique was cluster random sampling. The prerequisite test of normality, homogeneity, and balance before treatment showed that the data were normally distributed, homogeneous, and balanced. The prerequisite test for normality and homogeneity of the data after treatment showed that the data were normally distributed and homogeneous. The hypothesis test calculation using the t-test obtained of 2,2431 and with Î± = 5% ( ) of 1,6667. Based on the hypothesis testing results, the value of then is rejected; this means that the problem-solving ability of students who receive the MMP learning model is better than students who receive the Problem Solving learning model.